2018
DOI: 10.1097/corr.0000000000000542
|View full text |Cite
|
Sign up to set email alerts
|

Can an Augmented Reality Headset Improve Accuracy of Acetabular Cup Orientation in Simulated THA? A Randomized Trial

Abstract: Background Accurate implant orientation reduces wear and increases stability in arthroplasty but is a technically demanding skill. Augmented reality (AR) headsets overlay digital information on top of the real world. We have developed an enhanced AR headset capable of tracking bony anatomy in relation to an implant, but it has not yet been assessed for its suitability as a training tool for implant orientation. Questions/purposes (1) In the setting of simulated THA performed by novices, does an AR headset impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 45 publications
0
73
0
Order By: Relevance
“…42 The Although there were no differences in the final assessment between the AR-trained group and the surgeon-trained group, the AR guidance system may be useful in the education setting because it can provide feedback for motor skills required for arthroplasty without the need for attending surgeon oversight. 50 A related study by Cho et al 46 (Table 3). 6…”
Section: Augmented Reality (Ar)mentioning
confidence: 99%
See 1 more Smart Citation
“…42 The Although there were no differences in the final assessment between the AR-trained group and the surgeon-trained group, the AR guidance system may be useful in the education setting because it can provide feedback for motor skills required for arthroplasty without the need for attending surgeon oversight. 50 A related study by Cho et al 46 (Table 3). 6…”
Section: Augmented Reality (Ar)mentioning
confidence: 99%
“…In the fourth and final assessment, participants in both groups had improved to a comparable level (mean difference in accuracy between the two groups was 1.2°, 95% CI, −1.8° to 4.2°, P = .281). Although there were no differences in the final assessment between the AR‐trained group and the surgeon‐trained group, the AR guidance system may be useful in the education setting because it can provide feedback for motor skills required for arthroplasty without the need for attending surgeon oversight . A related study by Cho et al constructed a novel AR navigation system run on a tablet PC to aid in bone tumor resection.…”
Section: Applications In Orthopedic Surgerymentioning
confidence: 99%
“…28,29 Other new teaching methods Besides simulation training, other techniques exist to help in training of residents. Loghishetty et al 30 describe an augmented reality (AR) headset that can be used during total hip arthroplasty to improve accuracy of acetabular cup orientation. This study proved that the residents trained by AR were equally accurate compared to residents trained by a surgeon.…”
Section: Patient Safetymentioning
confidence: 99%
“…In terms of total knee arthroplasty (TKA), Pokhrel et al (28) proposed an AR-based system which might improve the accuracy of osteotomies, so that it might potentially improve the long-term outcomes of TKA. Logishetty et al (29) evaluated the use of AR for training medical students in acetabular cup placement for total hip arthroplasty, in a phantom pelvis. The participants were found to be equally accurate when trained either by an expert surgeon or AR.…”
Section: Preclinical Studies About the Use Of Augmented Reality In Ormentioning
confidence: 99%
“…The participants were found to be equally accurate when trained either by an expert surgeon or AR. As a result, the authors concluded that the latter method could be a valuable educational tool, since it was showed that some skills for arthroplasty can be learned without supervision (29). Fotouhi et al (30) noted that AR technology could lead to limited radiation, simple and accurate placement of acetabular implant during total hip arthroplasty.…”
Section: Preclinical Studies About the Use Of Augmented Reality In Ormentioning
confidence: 99%